2022
DOI: 10.1001/jamasurg.2022.4729
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Postoperative Antimicrobial Prophylaxis Use and Surgical Site Infection in Children Undergoing Nonemergent Surgery

Abstract: ImportanceUse of postoperative antimicrobial prophylaxis is common in pediatric surgery despite consensus guidelines recommending discontinuation following incision closure. The association between postoperative prophylaxis use and surgical site infection (SSI) in children undergoing surgical procedures remains poorly characterized.ObjectiveTo evaluate whether use of postoperative surgical prophylaxis is correlated with SSI rates in children undergoing nonemergent surgery.Design, Setting, and ParticipantsThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A recently published multicenter study across Europe found great heterogeneity regarding the duration of PAP, with a range from single dose PAP to 10 days [19]. In one study, standardization of perioperative antibiotic regimen in pediatric liver transplantation, gram‐negative broad‐spectrum antibiotic treatment for >48 h declined from 77% to 44% after implementation without an increase in infectious complications [31]. Our study found that prolonged PAP duration did not substantially reduce SSIs.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A recently published multicenter study across Europe found great heterogeneity regarding the duration of PAP, with a range from single dose PAP to 10 days [19]. In one study, standardization of perioperative antibiotic regimen in pediatric liver transplantation, gram‐negative broad‐spectrum antibiotic treatment for >48 h declined from 77% to 44% after implementation without an increase in infectious complications [31]. Our study found that prolonged PAP duration did not substantially reduce SSIs.…”
Section: Discussionmentioning
confidence: 55%
“…Results from adult trials cannot be extrapolated directly due to differing risk factors and physiological characteristics [30]. Furthermore, studies from nonimmunocompromised children that failed to identify benefit from PAP [31,32] cannot be directly transferred to children in the postoperative phase after LTx, which is characterized by high levels of immunosuppressants, often prolonged ventilation, use of vasopressors and sometimes associated wound healing disorders in the early postoperative phase. Prospective randomized controlled trials are warranted to identify optimal prevention bundles against SSIs at all stages and reduce antimicrobial exposure as well as reoperations.…”
Section: Discussionmentioning
confidence: 99%
“…A sufficient body of evidence now exists to broadly question the value of postoperative antibiotic prophylaxis in uncomplicated surgical procedures . For breast surgery, pediatric surgery, liver resection, cardiac surgery, pacemaker implantation, oromaxillofacial surgery, sarcoma resection, orthopedic surgery, and spine surgery, studies have shown no difference in SSI frequency when omitting or reducing the duration of postoperative antibiotic prophylaxis. In contrast, postoperative antibiotic durations longer than 24 hours have repeatedly been shown to be associated with increases in Clostridioides difficile infection, acute kidney injury, and antibiotic-resistant infection .…”
Section: Discussion and Observationsmentioning
confidence: 99%